2019
DOI: 10.1101/2019.12.28.890020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Replication timing maintains the global epigenetic state in human cells

Abstract: 5 6DNA is replicated in a defined temporal order termed the replication timing (RT) program. RT is 2 7 spatially segregated in the nucleus with early/late replication corresponding to Hi-C A/B 2 8 chromatin compartments, respectively. Early replication is also associated with active histone 2 9 modifications and transcriptional permissiveness. However, the mechanistic interplay between 3 0 RT, chromatin state, and genome compartmentalization is largely unknown. Here we report that 3 1RT is central to epigenome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Debatisse and Rosselli interpreted this suppression as due to earlier replication of fragile site DNA in lymphoblastoid cells in the absence of RIF1. The lack of any effect in our HCT116-based line may reflect cell line-specificity of RIF1 effects on replication timing ( Gnan et al, 2020 ; Klein et al, 2019 ).…”
Section: Discussionmentioning
confidence: 92%
“…Debatisse and Rosselli interpreted this suppression as due to earlier replication of fragile site DNA in lymphoblastoid cells in the absence of RIF1. The lack of any effect in our HCT116-based line may reflect cell line-specificity of RIF1 effects on replication timing ( Gnan et al, 2020 ; Klein et al, 2019 ).…”
Section: Discussionmentioning
confidence: 92%
“…Another concerted but only recently explained process is the conservation of replication timing order, which has been shown to orchestrate the global epigenetic state of individual cells. The principle behind this process is the continuation of previously established functional interpretation of the information stored in the genes (Klein et al, 2021), which follows our rationale. Beside random protein samples, we showed that even highly homologous groups of proteins categorized under different protein families' express more affinity towards proteome context than their family counterparts when being modeled semantically.…”
Section: Discussionmentioning
confidence: 98%
“…RT profiles make up a smaller subset of epigenomic predictors in our dataset and include mitotic cell lines that offer only limited representation of the diverse disease types in the pan-cancer cohort. Interestingly, DNA replication has been shown to determine chromatin state (44). Thus, the informative CA profiles of human cancers may represent a proxy of cancer-specific replication dynamics.…”
Section: Discussionmentioning
confidence: 99%